The potential of the Medical Digital Twin in diabetes management: a review - Chu, Yanting; Li, Shanhong; Tang, Jie; Wu, Huiqun (Frontiers in Medicine, 2023)
Diabetes is a prevalent chronic disease that must be managed in order to improve the patient's quality of life. However, the limited health care management resources compared to the large diabetes mellitus (DM) population is an obstacle which needs modern information technique to improve.Digital twin (DT) is a relatively new approach that has emerged as a viable tool in several sectors of healthcare, and there have been some publications on DT in disease management. While the systematic summary of the use of DTs and its potential applications in DM is less reported. In this review, we summarized the key techniques of DTs and proposed those potentials in DM management from different aspects and discussed the concerns of this novel technique in DM management.